Radioimmunotherapy of Blastomycosis in a Mouse Model With a (1→3)-β-Glucans Targeting Antibody - Helal, Muath; Allen, Kevin J. H.; van Dijk, Bruce; Nosanchuk, Joshua D.; Snead, Elisabeth; Dadachova, Ekaterina (Frontiers in Microbiology, 2020)
Invasive fungal infections (IFI) cause devastating morbidity and mortality, especially in organ transplant patients, cancer patients and patients in intensive care units, with the number of IFIs more than tripling since 1979. Radioimmunotherapy (RIT) utilizes antigen-antibody interaction to deliver lethal doses of ionizing radiation to cells and has demonstrated efficacy in several types of cancer. Our laboratories were the first to demonstrate that microorganism-specific monoclonal antibodies are highly effective in treatment of experimental fungal, bacterial and viral infections. Later we proposed to utilize surface expressed antigens shared by major IFI-causing pathogens such as melanin, heat shock protein 60 (HSP60) and beta-glucans as targets for radiolabeled antibodies. Here we evaluated in vivo RIT targeting pan-antigens in IFIs. Blastomycosis dermatitidis was chosen as a model for this work as it causes serious infections in immunocompromised patients, immunocompetent individuals and in companion dogs. B. dermatitidis cells were treated with the 400-2 antibody to (1→3)-β-glucans which was radiolabeled with the beta particles emitter 177Lutetium (177Lu) and alpha particles emitter 213Bismuth (213Bi) and the efficacy of cell kill was determined by CFUs. To determine the antigen-specific localization of the 400-2 antibody in vivo, C57BL6 mice were infected intratracheally with 2×105 B. dermatitidis cells and given 111In-400-2 antibody 24 hr later. To evaluate the killing of B. dermatitidis cells with RIT, intratracheally infected mice were treated with 150 µCi 213Bi-400-2 and their lungs analyzed for CFUs 96 hrs post-infection. 213Bi-400-2 proved to be more effective in killing B. dermatitidis cells in vitro than 177Lu-400-2. Three times more 111In-400-2 accumulated in the lungs of infected mice, than in the non-infected ones. 213Bi-400-2 lowered the fungal burden in the lungs of infected mice more than 2 logs in comparison with non-treated infected controls. In conclusion, our results demonstrate the ability of an anti-(1-3)-beta-D-glucan antibody armed with an alpha-emitter 213Bi to selectively kill B. dermatitidis cells in vitro and in vivo. These results provide strong evidence of the effectiveness of RIT targeting pan-antigens on fungal pathogens.